Total endograft replacement of aortic arch - Neequaye, Simon; Abraham, Cherrie Z. (Annals of Cardiothoracic Surgery, 2013)
Total endovascular replacement of the aortic arch is a complex procedure that is often favoured when the pathology anatomy precludes a standard median sternotomy. Here we present the case of endograft repair in a 79 year old male with 6.5 cm arch aneurysm and 5.4 cm descending thoracoabdominal aneurysm. Following bilateral carotid-subclavian bypasses, a long 7 Fr sheath was advanced into the descending aorta through the common iliac artery purse string. A double curved long Lunderquist wire was guided to deep within the left ventricle, and the endograft carefully advanced over the wire. The graft was radiologically orientated, and deployed under asystolic conditions. Retrograde cannulation of the branches were accomplished, with carotid sheath placed into the branches followed by bridging stents. The graft delivery system was then removed. This approach obviates the need for a sternotomy, cumbersome extra-anatomic debranching, and hypothermic circulatory arrest.